1995
DOI: 10.1080/08886504.1995.10782142
|View full text |Cite
|
Sign up to set email alerts
|

Focusing Attention with Temporal Sound

Abstract: This research addressed the problem of students' inattention to critical information from ti:Je computer interface by focusing on software solutions using sound. Current interest in constructivism, hypermedia authoring, and verbal-information learning suggested endorseme'1t of these areas as the experimental platform. Temporal sound was designated for empirical study. Temporal sound is spoken information provided about future and past events that prese.'lt highlights and details about static or moving visuals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Hence, students in the static graphic group are more likely to engage in the powerful organizational properties of an image system [8,14]. Animation might direct a learner's attention, but learners might not be able to perceive the meaning or attend to the details of the display without proper guidance [2,18,31]. Subjects given animated presentation alone might concentrate on irrelevant visual features thus hindering association of the analogy provided [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, students in the static graphic group are more likely to engage in the powerful organizational properties of an image system [8,14]. Animation might direct a learner's attention, but learners might not be able to perceive the meaning or attend to the details of the display without proper guidance [2,18,31]. Subjects given animated presentation alone might concentrate on irrelevant visual features thus hindering association of the analogy provided [10].…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid progress of computer audiovisual techniques, it has become an important concern whether the use of audio, visual, or the combination of both channels can actually facilitate the process of computer-based learning [1,2]. Previous research found that for learning abstract concepts, static graphics provides more chances to build connections between the concrete and abstract domains [3].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the stochastic roles for sound, Downloaded by [University of Kent] at 10:51 04 December 2014 the SSF model is derived from design principles, discussed later in the paper. The origins and applications of the SSF model are explained in Mann (1992Mann ( , 1995aMann ( , 1995bMann ( , 1996.…”
Section: The Ssf Modelmentioning
confidence: 99%
“…Previous research has shown that adults and older adolescents (i.e. apprentices, college and university students) learn better from educational multimedia when critical information is presented in speech rather than on‐screen text (Chandler & Sweller, 1992; Mann, 1995a; Mann, 1997a; Mayer, 1997; Moreno & Mayer, 2000). A study with 78 college students (Mayer & Moreno, 1998) reported enhanced learning when the instructional material did not require them to split their attention between multiple sources of mutually referring information.…”
Section: Introductionmentioning
confidence: 99%